Nihon Shuwa (日本手話): How the Deaf Fight and Sign Through Barriers in Japan - Tarisya Maharani Ohorella; Ghulam Phasa Pambayung (Department of International Relations, Brawijaya University, 2023)
When talking about inclusive society, one should ponder the point of creating a society that provides equal opportunities regardless of the backgrounds of its members. An identity background one can have is to be hearing-impaired. Promoting inclusive society also means eradicating any hindrance faced by them. A number of countries have tried to do so, with many having failed. In that case, Japan is another case where the government is trying their best to design an inclusive society. Through this paper, the writers will try to elaborate the condition and struggle that is faced by the Deaf of Japan. Using Tan and Ang inclusive society characteristic as a theoretical framework, the writers found that, despite the fact that there has been efforts made by the government of Japan to integrate Deaf people into its society, namely by introducing Japanese Sign Language (JSL) and national Deaf organization, they has not been able to create inclusive society for the deaf. Their struggle is simply not enough to face problems such as the scarcity of Deaf educational institutions, interpreters, and representations. Despite there has been many studies examining the identity and struggles of the Deaf in Japan, the writers consider this writing as a precious contribution to inclusivity studies. KEYWORDS: Deaf community; sign language; inclusivity; Japan